The Intervention of Government in Rector Selection and Its Impact on Academic Freedom in Higher Education Institutions - Rizqiyanto, Naufal; Sangadji, Sulastri; Hendrawan, Rikki (CV. Pustaka Parawali, 2025)
Regulation of the Minister of Research, Technology, and Higher Education (Permenristekdikti) No. 19/2017 on the Appointment and Dismissal of Leaders of State Universities indicates that the Minister of Education and Culture holds 35% voting rights to elect rectors, while the university senate holds 65% voting rights. This percentage is prone to emasculating the majority vote in universities. It has an impact on the rise of high-level lobbying ahead of the rector selection, both to political parties and to the Palace. This kind of practice undermines the independence of state universities in channelling aspirations to address the state's social issues. This research contributes to the analysis of the dynamics of rector selections in Indonesia, examining the impact of government intervention on rector independence and freedom of speech, and proposing an ideal regulatory framework based on transparency, meritocracy, and autonomy. It fills a gap in existing studies by highlighting how ministerial voting rights affect academic freedom and offering a reform-oriented model for more democratic and independent university leadership. This research is a normative juridical study that employs statutory, conceptual, and case study approaches to address the problem. The results showed that, first, government intervention in the selection of rectors is problematic in a democratic country, Second, government intervention in the selection of rectors has a significant effect on the independence of freedom of higher education in responding to social issues of state, Third, Changing the provisions of government intervention in the selection of rectors in State Universities by emphasizing transparency aspects, meritocracy and independence.